Ioane Petritsi and His Philosophical-theological Project - Levan Gigineishvili, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
Ioane Petritsi holds a special place in Georgian intellectual culture, along with such figures as Shota Rustaveli, Solomon Dodashvili, Nikoloz Baratashvili and Ilia Chavchavadze. Those names signify breaking through certain world-view stereotypes, escaping frames of tradition, modifying the tradition through the light of new knowledge and experience. Any tradition, unless it is creatively rethought through the light of universal intellectual processes and developments of this or that epoch, leaves no space for an explosion and continues to turn in circles. Such thinkers as Petritsi bear a credit of cutting through and opening such circles. In particular, Petritsi introduced into Georgian intellectual culture philosophy in the initial, Classical meaning of this notion. This notion implies a natural human propensity, striving, desire to understand and explain the universe not through some ready-made outer schemes (religious, ideological, cultural), but through one's own intellectual efforts, through actualization of one's own innate intellectual principle. This actualization was called by Greeks dialectics, and it has its own order and culture. Dialectics, although the term carries much ambiguities, can be defined as a dynamic space of objective thinking, in which a person who is involved in dialectic process of thought believes that through this method he or she comes out from a particular, personal, subjective space and thinks as all humanity would have thought, that is to say, universally.